Financial Distress and Psychological Well-Being During the Covid-19 Pandemic - Droller, F (Frontiers Media S.A., 2022)
Objective: We examine the impact of financial distress caused by the COVID-19 pandemic on mental health and psychological well-being. Methods: We analyze cross-sectional survey data (n = 2,545) from the Life during Pandemic study in Chile. We estimate linear probability models to analyze the relationship between economic fragility, financial distress, and psychological well-being. Results: Our findings show unemployment and income loss are highly predictive of experiencing a range of financial problems, such as a lack of savings, as well as difficulties paying bills, consumer debt, and mortgage loans. In turn, financial distress leads to a higher prevalence of poor well-being and mental health deterioration, and sleep problems. Conclusion: Expansion of mental health assistance services are needed, as new diagnosis of mental health conditions has increased, but treatment has not, pointing to a barrier in the access to some mental health care services during the pandemic. Policies designed with the objective of improving financial education are necessary to increase precautionary savings and financial resilience, and alleviate the psychological burden of debt in the future. Copyright © 2022 Borrescio-Higa, Droller and Valenzuela.